Information usefulness of public disclosure in Taiwan: Does it vary across specific diseases/conditions and contexts? - Tsung-Tai Chen; Kai-Ren Chen; Ming-Hsin Phoebe Chiu; Chih-Kuang Liu; Wei-Chih Su; Vinchi Wang (PLoS ONE, 2025)
Objectives This study discusses issues regarding tailored information for report cards, including what kinds of information patients with different diseases need and how the necessary information changes for these patients given alterations to a specific context. This study aimed to determine whether there is consistent, essential quality information across different diseases and in diverse contexts. The priority of needs related to interpersonal and technical quality information for different diseases is also discussed. Methods Fifty-five patients from 5 hospitals in Taiwan were interviewed or invited to participate in a focus group. Patients were diagnosed with five different diseases or conditions: stroke, dialysis, AMI, diabetes, and knee problems. We conducted in-depth interviews to identify the most requested types of information for every disease or condition in general and in different contexts (e.g., relocation). We applied the Kano model to verify the relative priority of the information that emerged from the interviews for each disease. Results The 3 most requested types of information among patients with various diseases or conditions in the general context were medical professionalism, physician communication skills, and accessibility. Only a few types of information were valued by patients with specific diseases. In addition, patients focused on specific and mutually relevant information in certain contexts (e.g., in the context of conflict with physicians, patients considered communication skills most important). This information was similar to the 3 most common types of information in the general context regardless of the disease, with the exception of stroke. Finally, technical quality information was treated as basic or necessary information. However, most important information was treated as expected information regardless of the disease. Conclusions There is somewhat consistent essential quality information across different diseases and diverse contexts. According to the results of the Kano model, the report card should disclose interpersonal and technical quality simultaneously.